Politainment dan Masyarakat Penonton: Analisis Wacana Kritis Norman Fairclough pada Pemberitaan akun @Tempo.co - Fuandani Istiati; Kamila Salsabela (Jurnal Ilmu Komunikasi AKRAB, 2026)
The development of social media, particularly Instagram, has significantly transformed the fundamental landscape of communication. One notable transformation can be observed in political communication, which is no longer limited to the exchange of messages, symbols, and meanings concerning power, public interests, and political decision-making processes, but has increasingly evolved into a form of entertainment among audiences. The phenomenon of politainment demonstrates how political issues, actors, and events are packaged as spectacles designed to attract audience attention. Employing Norman Fairclough’s critical discourse analysis, this study examines how the consumption of political information and messages has increasingly become a form of entertainment among the public and contributes to the emergence of negative responses. The data consist of several political news posts published on the @Tempo.co Instagram account concerning Raffi Ahmad, particularly those featuring dramatic visual representations. The study further examines the processes through which discourse is produced and consumed within the dynamics of @Tempo.co’s posts, as well as how these practices are associated with power relations, media ideology, and contemporary popular culture. This study is expected to provide insight into the transformation of political discourse beyond its conventional journalistic function.